2011
DOI: 10.1002/em.20649
|View full text |Cite
|
Sign up to set email alerts
|

Malathion and fenvalerate induce micronuclei in mouse bone marrow cells

Abstract: Health effects of pesticides are a major public health concern. In this study, the genotoxic effects of two commonly-used pesticides, malathion, and fenvalerate, were investigated in mice in vivo. Induction of micronuclei in bone marrow cells was used as the test parameter following exposure to 2.5, 5 or 10 mg/kg malathion by intraperitoneal (i.p.) or per oral (p.o.) exposure. Exposure by both routes was found to cause a significant increase in micronucleated polychromatic erythrocytes (PCEs) in a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous studies have affi rmed the genotoxic and/or cytotoxic effects of Type II pyrethroids such as cyfl uthrin, cypermethrin etc. (4)(5)(6)(7)(8)(9). The carcinogenic potential of pyrethroids was also reported on the murine model (9).…”
mentioning
confidence: 86%
“…Previous studies have affi rmed the genotoxic and/or cytotoxic effects of Type II pyrethroids such as cyfl uthrin, cypermethrin etc. (4)(5)(6)(7)(8)(9). The carcinogenic potential of pyrethroids was also reported on the murine model (9).…”
mentioning
confidence: 86%
“…Swiss albino mice strains exposed to malathion evidenced bone marrow cell metaphases with various types of chromosomal alterations, and the pesticide-induced significantly higher frequency of alterations (p<0.001) in the three acute doses tested (2.5, 5 and 10mg/ kg) than in control, besides increased frequencies of sister chromatid exchanges and sperm head anomalies 59 . Giri et al 54 reported the dose-dependent increased frequency of micronucleated polychromatic erythrocytes in bone marrow cells of mice of the same species after in vivo exposure to malathion at 95% purity.…”
Section: Malathionmentioning
confidence: 99%